Comparative evaluation of different marketed products of ciprofloxacin tablets in vitro - Mus Mus; ab M. Khalaf; Hiyam A Al-Taii; Imad A-J Thanoon (University of Mosul, 2010)
The contents of four ciprofloxacin tablets products available in the private pharmacies of Mosul city were measured according to the British Pharmacopoeia (BP). Some biopharmaceutical parameters such as content uniformity, disintegration, and hardness were also measured for the same products. In addition, the antibacterial activity of these four products were assessed by microbiological assay on different types of gram negative bacteria in vitro. The results indicated that there is a little differences in the content uniformity of these products and they are within acceptable requirement of BP and United State Pharmacopoeia (USP). In the same manner, the weight variation, disintegration, and hardness were within acceptable range according to the BP and USP. The microbiological assay indicated that these different products produce approximately the same inhibition zones on the same bacterial type. The above results may be useful to predict the bioavailability of these different products .